Hubungan Lama Menjalani Hemodialisis Dengan Status Gizi Pasien Gagal Ginjal Kronis yang Menjalani Hemodialisis Reguler di RSUD Sanjiwani Gianyar - Anak Agung Gede Budhitresna; Putu Arya Suryandhita; Dewa Gde Agung Wikananda Besang (Aesculapius Medical Journal, 2023)
One of the most often seen condition in Chronic Kidney Failure patients that undergo regular hemodialysis is decreasing nutritional status with the length of time these patients underwent therapy. This study aims to determine the relationship between the duration of undergoing hemodialysis and nutritional status of chronic kidney failure patients undergoing regular hemodialysis at the Sanjiwani Hospital, Gianyar. This study uses analytical method and a cross-sectional approach. Data was taken at Sanjiwani Hospital, Gianyar with a medical record data recording form. The sample were patients that underwent hemodialysis regularly at hemodialysis unit of the Sanjiwani Hospital Gianyar using a criterion that had been chosen using the sampling technique, which is purposive sampling. Chi-Square Test was used to assess the relationship of the variables. The results showed that most of the chronic kidney failure patients who underwent regular hemodialysis at the Sanjiwani Hospital, Gianyar, in this study underwent hemodialysis for less than 3 years, which is 52.2%. Chronic kidney failure patients who underwent regular hemodialysis at the Sanjiwani Hospital Gianyar in this study had a normal nutritional status of 40%, 26,7% patients are underweight, 20% patients are pre-obesity, 11,1% patients are obesity I, and 2,2% patients are obesity II. Chi-Square test result showed that there was a significant relationship between length of time undergoing hemodialysis and nutritional status of chronic kidney failure patients undergoing regular hemodialysis at the Sanjiwani Hospital, Gianyar (p = 0.011).